Fathers' Involvement in Early Childhood Education: Navigating Parenting with Working Mothers in the Digital Age - Feunika Apsira Sutrisno; Diana Diana; Edi Waluyo (STAI Hubbulwathan Duri, 2025)
Social skills are a key component of early childhood social-emotional development. This study investigates the influence of gadget usage intensity, parenting patterns of working mothers, peer interaction, and the moderating role of father involvement on early childhood social development.This explanatory research employed a quantitative approach, targeting kindergarten teachers and students in Mayong District, Jepara Regency. Using proportionate random sampling, 100 participants were selected. Data were collected through questionnaires and analyzed using multiple regression analysis with moderation testing.Findings revealed that gadget usage intensity (p = 0.041), working mothers' parenting patterns (p = 0.017), and peer interaction (p = 0.040) significantly affected early childhood social development. Father involvement significantly moderated the effect of working mothers' parenting patterns (p = 0.047), strengthening their influence on children’s social development. However, father involvement did not moderate the impact of gadget usage (p = 0.184) or peer interaction (p = 0.449).The results suggest that balanced parenting and peer interaction are crucial for early childhood social development, and father involvement can enhance maternal parenting effectiveness. In contrast, excessive gadget use remains a risk factor.Parental supervision, particularly in gadget use, is essential. Schools should implement interactive group activities to support children’s social skills. Future studies should explore additional influencing factors, such as family support and parent-child communication, to provide a more comprehensive understanding of early childhood social development.